Pengaruh Rasio Diameter Inti High-Damping Rubber terhadap Kekakuan Horizontal dan Rasio Redaman Isolator Elastomerik pada Regangan Geser 150% - Dimas Rizky Tanaya; Ahmad Basshofi Habieb (RESWARA: Jurnal Riset Ilmu Teknik, 2026)
Lead cores are commonly used in seismic isolators to enhance energy dissipation; however, their toxicity and environmental impact have encouraged the development of lead-free alternatives. This study evaluates the effect of the High-Damping Rubber (HDR) core diameter ratio on the horizontal stiffness and equivalent damping ratio of elastomeric seismic isolators subjected to 150% shear strain. Three specimen configurations were examined: A1 without an HDR core, B1 with a 40 mm HDR core, and C1 with an 80 mm HDR core. All specimens had an outer diameter of 200 mm and consisted of eleven 4 mm rubber layers reinforced by ten 2 mm steel plates. Displacement-controlled cyclic lateral tests were conducted. Horizontal stiffness was calculated from the maximum and minimum force-displacement responses, while the equivalent damping ratio was obtained from the hysteresis-loop area. The horizontal stiffness values of A1, B1, and C1 were 0.61, 0.57, and 0.48 kN/mm, respectively, and their equivalent damping ratios were 6.89%, 9.18%, and 10.27%. Compared with A1, the stiffness of B1 and C1 decreased by 6.56% and 21.31%, whereas their damping ratios increased by 33.24% and 49.06%. Increasing the HDR core diameter ratio produced a more flexible isolator with improved damping performance.